Polymer Based Bioadhesive Biomaterials for Medical Application-A Perspective of Redefining Healthcare System Management - TOKSOY ÖNER, EBRU (MDPI, 2020)
This article deliberates about the importance of polymer-based bioadhesive biomaterials' medical application in healthcare and in redefining healthcare management. Nowadays, the application of bioadhesion in the health sector is one of the great interests for various researchers, due to recent advances in their formulation development. Actually, this area of study is considered as an active multidisciplinary research approach, where engineers, scientists (including chemists, physicists, biologists, and medical experts), material producers and manufacturers combine their knowledge in order to provide better healthcare. Moreover, while discussing the implications of value-based healthcare, it is necessary to mention that health comprises three main domains, namely, physical, mental, and social health, which not only prioritize the quality healthcare, but also enable us to measure the outcomes of medical interventions. In addition, this conceptual article provides an understanding of the consequences of the natural or synthetic polymer-based bioadhesion of biomaterials, and its significance for redefining healthcare management as a novel approach. Furthermore, the research assumptions highlight that the quality healthcare concept has recently become a burning topic, wherein healthcare service providers, private research institutes, government authorities, public service boards, associations and academics have taken the initiative to restructure the healthcare system to create value for patients and increase their satisfaction, and lead ultimately to a healthier society.
Keywords: bioadhesion; biomaterials; biomedical application; healthcare system management; innovation; polymer based bioadhesive; BACTERIAL CELLULOSE; CRYPTOMPHALUS-ASPERSA; HALOMONAS-SMYRNENSIS; MULTILAYER FILMS; SULFATED LEVAN; CHITOSAN; SECRETION; BIOCOMPATIBILITY; CHILOPODA; COATINGS